Ab initio Study of Anchoring Groups for CuGaO2 Delafossite-Based p-Type Dye Sensitized Solar Cells - Muñoz-García, Ana B.; Caputo, Laura; Schiavo, Eduardo; Baiano, Carmen; Maddalena, Pasqualino; Pavone, Michele (Frontiers in Chemistry, 2019)
Here we report the first theoretical characterization of the interface between the CuGaO2 delafossite oxide and the carboxylic (-COOH) and phosphonic acid (-PO3H2) anchoring groups. The promising use of delafossites as effective alternative to nickel oxide in p-type DSSC is still limited by practical difficulties in sensitizing the delafossite surface. Thus, this work provides atomistic insights on the structure and energetics of all the possible interactions between the anchoring functional groups and the CuGaO2 surface species, including the effects of the Mg doping and of the solvent medium. Our results highlight the presence of a strong selectivity toward the monodentate binding mode on surface Ga atoms for both the carboxylic and phosphonic acid groups. Since the binding modes have a strong influence on the hole injection thermodynamics, these findings have direct implications for further development of delafossite based p-type DSSCs.